Too many bosses, too few leaders the three essential principles you need to become an extraordinary leader - Peshawaria, Rajeev (Free Press, 2011)
Outlines a program for achieving consistent leadership excellence, explaining the definition of true leadership while sharing stories about effective role models from such companies as Coca-Cola, American Express, and Morgan Stanley